2017
DOI: 10.3389/fpls.2017.02176
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of the Histone Acetyltransferase GCN5 through Alternative Splicing in Brachypodium distachyon

Abstract: The epigenetic modulatory SAGA complex is involved in various developmental and stress responsive pathways in plants. Alternative transcripts of the SAGA complex's enzymatic subunit GCN5 have been identified in Brachypodium distachyon. These splice variants differ based on the presence and integrity of their conserved domain sequences: the histone acetyltransferase domain, responsible for catalytic activity, and the bromodomain, involved in acetyl-lysine binding and genomic loci targeting. GCN5 is the wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 83 publications
(161 reference statements)
0
11
0
Order By: Relevance
“…While human Brd-homologs are important in several molecular mechanisms (Sanchez and Zhou, 2009; Sanchez et al, 2014; Filippakopoulos et al, 2012; Taniguchi, 2016; Cochran et al, 2019; Morgado-Pascual et al, 2019; Uppal et al, 2019; Boyson et al, 2021), only few plant Brd-homologs have been analyzed, including BRD-ET proteins of A. thaliana (GTE1/IMB1, Duque and Chua, 2003; GTE6, Chua et al 2005; GTE4, Airoldi et al, 2010; GTE9; GTE 11, Misra et al 2017), B. distachyon GCN5 (Martel, et al, 2017), and N. benthamiana NbDBCP (Sukarta et al 2020). The plant Brd-homologs with multi-domain architecture, are likely to be involved in diverse cellular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While human Brd-homologs are important in several molecular mechanisms (Sanchez and Zhou, 2009; Sanchez et al, 2014; Filippakopoulos et al, 2012; Taniguchi, 2016; Cochran et al, 2019; Morgado-Pascual et al, 2019; Uppal et al, 2019; Boyson et al, 2021), only few plant Brd-homologs have been analyzed, including BRD-ET proteins of A. thaliana (GTE1/IMB1, Duque and Chua, 2003; GTE6, Chua et al 2005; GTE4, Airoldi et al, 2010; GTE9; GTE 11, Misra et al 2017), B. distachyon GCN5 (Martel, et al, 2017), and N. benthamiana NbDBCP (Sukarta et al 2020). The plant Brd-homologs with multi-domain architecture, are likely to be involved in diverse cellular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In both plants, the duplication and AS-events enhanced the heterogeneity of the Brd-homologs. AS-events were also shown to responsible for the differential fate and interaction of two GCN5 isoforms with similar localization (Martel et al, 2017). Therefore, understanding the significance of AS-events of At/OsBrds-homologs is important, as in certain cases AS-isoforms (e.g., OsBrd1.2, lacks BRD) are more abundant than the CS-isoforms, in both tissue- and stress-specific environment (Supplementary Figure 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, alternative splicing in GCN5 transcripts have been reported in humans as well as Brachypodium distachyon (i.e., GCN5 , L-GCN5 , and S-GCN5 splice variants) [ 92 ], in which GCN5 and L-GCN5 but not S-GCN5 could interact with ADA2, indicating that these isoforms function in the diversification of the SAGA complex association, and shed light on the differences in the protein organization of plant GCN5-containing complexes [ 92 ]. Thus, plants may hold compositionally distinct SAGA-like complexes based on the different histone acetyltransferase subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Plants studies have mainly focused on Arabidopsis , in which 29 BRD proteins have been identified [ 10 ] and functions of only three genes, from among 12, have been characterized [ 11 ]. Brachypodium [ 12 ], tomato and tobacco species [ 13 ] as well as soybean [ 10 ] have also been analyzed. Although researches related to plant bromodomains are ongoing, there is still no evidence to support the Florence and Faller [ 14 ] hypothesis explaining the presence of one bromodomain in plant proteins instead of two, as is the case in animals.…”
Section: Introductionmentioning
confidence: 99%